2014
DOI: 10.3109/14992027.2014.972524
|View full text |Cite
|
Sign up to set email alerts
|

Dietary habits and hearing

Abstract: The study indicates that diet is important for aural health in aging. According to this study fish is beneficial to hearing, whereas consumption of "junk food", rich in low molecular carbohydrates, is detrimental. Other correlations, e.g. between high consumption of antioxidants, were not demonstrated here, but cannot be excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…A greater number of studies demonstrated significant associations between dietary factors and hearing loss. A diet high in oily fish (10,12,13) , n-3 fatty acids (10,12) , vitamins and antioxidants (14,(16)(17)(18)24) and moderate alcohol consumption (19) has been associated with a reduced risk of hearing loss, which supports our finding that a healthier diet is associated with reduced risk of hearing loss. Conversely, a high cholesterol intake (21) and a high intake of foods with a high glycaemic load (22) have been associated with an increased risk of hearing loss.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A greater number of studies demonstrated significant associations between dietary factors and hearing loss. A diet high in oily fish (10,12,13) , n-3 fatty acids (10,12) , vitamins and antioxidants (14,(16)(17)(18)24) and moderate alcohol consumption (19) has been associated with a reduced risk of hearing loss, which supports our finding that a healthier diet is associated with reduced risk of hearing loss. Conversely, a high cholesterol intake (21) and a high intake of foods with a high glycaemic load (22) have been associated with an increased risk of hearing loss.…”
Section: Discussionsupporting
confidence: 86%
“…This has prompted investigation into the possibility that certain nutrients and foods may also be associated with the incidence of hearing loss. Higher intake of n -3 fatty acids ( 10 , 12 ) , oily fish ( 10 , 12 , 13 ) , Mg ( 14 ) , vitamin intake, including vitamins A ( 15 ) , B 12 (16 18 ) C ( 14 ) and E ( 15 ) , antioxidant intake, including β -carotene ( 14 ) , and moderate alcohol consumption ( 19 ) have been associated with a lower incidence of hearing loss. Conversely, Shargorodsky et al ( 20 ) found that the overall intake of vitamins C, E and β -carotene was not associated with the incidence of hearing loss in men.…”
mentioning
confidence: 99%
“…It has been suggested that diet quality plays a role in the relation between body composition and age-related hearing loss. Studies observed a relation between food groups, such as fish and carbohydrates consumption, and hearing thresholds [1214]. However, many complex interactions occur across different food components and nutrients [15] which triggered the interest to study effects of dietary patterns as a whole [15].…”
Section: Introductionmentioning
confidence: 99%
“…Various nutrients have been reported to be associated with hearing impairment 6,35,3739 . Some studies showed an association between factors depicting the general nutrition status, such as body indices or serum albumin levels, and hearing impairment 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Kang et al ., who analyzed a cohort similar to ours, showed that the levels of micronutrients, including vitamins C and D, are associated with hearing thresholds 6 . Some reports showed associations between dietary patterns and hearing 35,39 . Prospective or cross-sectional studies examining the association between nutrients and hearing impairment may be on-going.…”
Section: Discussionmentioning
confidence: 99%